What systemic racism in Canada looks like - CBC News (2020)
The police killing of George Floyd and the protests that followed have brought renewed attention to systemic racism. In Canada, some have been quick to deny its existence. But these experts say racism has been normalized within Canadian institutions. Producer: Avneet Dhillon Research: Britnei Bilhete, Alisha Parchment Production editor: Charles Fogel Graphic designer: Thomas Hall Senior producer: Roxanna Woloshyn Executive producer: Irene Thomaidis For more stories about the experiences of Black Canadians — from anti-Black racism to success stories within the Black community — check out Being Black in Canada here: https://www.cbc.ca/beingblackincanada »»» Subscribe to CBC News to watch more videos: http://bit.ly/1RreYWS Connect with CBC News Online: For breaking news, video, audio and in-depth coverage: http://bit.ly/1Z0m6iX Find CBC News on Facebook: http://bit.ly/1WjG36m Follow CBC News on Twitter: http://bit.ly/1sA5P9H For breaking news on Twitter: http://bit.ly/1WjDyks Follow CBC News on Instagram: http://bit.ly/1Z0iE7O Download the CBC News app for iOS: http://apple.co/25mpsUz Download the CBC News app for Android: http://bit.ly/1XxuozZ »»»»»»»»»»»»»»»»»» For more than 75 years, CBC News has been the source Canadians turn to, to keep them informed about their communities, their country and their world. Through regional and national programming on multiple platforms, including CBC Television, CBC News Network, CBC Radio, CBCNews.ca, mobile and on-demand, CBC News and its internationally recognized team of award-winning journalists deliver the breaking stories, the issues, the analyses and the personalities that matter to Canadians.
Keywords: amériques; approches et analyses; canada; cours; histoire et politique; pol5480; premier cycle; pédagogie; racisme; régions géographiques; systèmes d'oppressions; thématiques; violences